The Ability to Understand Indonesian Language Equivalents Among Private Universities Students in Jakarta - Hilda Hilaliyah; Fajar Kurniadi; Tanti Dwi Oktaviany (Universitas Indraprasta PGRI, 2021)
This study aims to determine the ability of students to understand the Indonesian equivalent in using Indonesian vocabulary. The method used in this research is descriptive qualitative method. The results of this study are the low use of Indonesian equivalent words among students, it is proven that at least 98% of respondents hear and use the word Laundry more often than the word penatu. In addition, there is a lack of habituation to the use of equivalent words in the academic environment and society. This is evidenced by several words that are closely related to the academic environment and people still use words in foreign languages, even though their equivalent words have been found and socialized.Keywords: Word Match, Indonesian Language, Student.